Fiziceskaja rabotosposobnost' i stress-vosstanovlenie u lyžnikov-gonšcikov v podgotovitel'nyj i sorevnovatel'nyj period - Garnov, I. O.; Calyševa, A. A.; Varlamova, N.G.; Loginova, T. P.; Bojko, E. R. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The influence of the preparatory and competitive period on the functional and psychological state of 11 skiers-racers has been explored. In the research we used a test to failure on a bicycle ergometer and a questionnaire "Stress-Recovery - Questionnairefor Athletes - 76". It was shown that in the competitive stage, in comparison with the preparatory period, along with a significant increase in the level of the "Injury scale", physiological indicators of skiers decreased (including the percentage of oxygen consumption at the anaerobic threshold relative to the maximum oxygen consumption and cardiorespiratory indices).